Sustainable healthy diets in China: a multidimensional framework and assessment - Zhu, Wenbo; Han, Xinru; Liu, Yang; Li, Guojing; Wen, Jinshang (Frontiers in sustainable food systems, 2024)
In China, the urgent need to formulate food policies that address both nutritional health and climate challenges has become increasingly apparent. This study constructs a theoretical framework and a multi-objective programming model that takes into account income disparities, aiming to delineate a sustainable healthy diet for Chinese residents and pinpoint key areas for dietary transformation. Our findings reveal that a sustainable healthy diet in China should involve moderate adjustments to staple foods, such as reducing rice consumption in favor of alternatives like flour and other grains. The diet should emphasize low-fat consumption, increased intake of fruits and vegetables, and a balanced intake of animal products by reducing meat, poultry, eggs, and fish, while ensuring sufficient consumption of chicken, shrimp, and dairy products. Furthermore, it recommends reducing alcohol consumption and limiting high-calorie snacks like cakes. This proposed diets achieves multiple objectives: it can reduce greenhouse gas emissions from the food system by 12.8%, decrease food expenditure by 1.1%, and significantly improve dietary quality. However, the study also highlights a trade-off between consumer interests and environmental benefits across different income groups. For the low-income group, minimal dietary changes result in a 2.0% increase in food expenses and an 11.1% increase in greenhouse gas emissions. Conversely, while the diet may slightly misalign with the preferences of middle and high-income groups, these groups benefit from reductions in food expenses (ranging from 0.4 to 4.8%) and greenhouse gas emissions (ranging from 14.5 to 23.4%). Thus, initiating reforms from the consumer end of the food system and guiding dietary patterns towards a healthier and more sustainable pattern through targeted food policies could be a crucial strategy for addressing nutritional and environmental challenges. However, it is essential to balance environmental benefits with ensuring the welfare of different income groups within China’s diverse economic landscape. This calls for differentiated policies to safeguard the wellbeing of the population.